The holography of non-invertible self-duality symmetries - Andrea Antinucci; Francesco Benini; Christian Copetti; Giovanni Galati; Giovanni Rizi (Journal of High Energy Physics)
Abstract We study how non-invertible self-duality defects arise in theories with a holographic dual. We focus on the paradigmatic example of su N $$ \mathfrak{su}(N) $$ N $$ \mathcal{N} $$ = 4 SYM. The theory is known to have non-invertible duality and triality defects at τ = i and τ = e 2πi/3, respectively. At these points in the gravitational moduli space, the gauged SL(2, ℤ) duality symmetry of type IIB string theory is spontaneously broken to a finite subgroup G, giving rise to a discrete emergent G gauge field. After reduction on the internal manifold, the low-energy physics is dominated by an interesting 5d Chern-Simons theory, further gauged by G, that we analyze and which gives rise to the self-duality defects in the boundary theory. Using the five-dimensional bulk theory, we compute the fusion rules of those defects in detail. The methods presented here are general and may be used to investigate such symmetries in other theories with a gravity dual.